A comparative study about mobile learning with gamification and augmented reality in high education institutions across South Europe, South America, and Asia countries - Durão, Natércia (2019)
In current context, the society is being transforming itself in what genetically is named as digital society. The digital is taking over the organizations that perceive in technology an advancement/added value for their business. In the context of higher education as part of society, it is thus "forced" to change its operant mode in general and in particular in the teaching- learning process making it more digital, and at the same time more motivating for students. The aim of this study is to investigate the perception that higher education professors in the area of technology, across South Europe, South America, and Asia countries have about the use of mobile technologies such as gamification and augmented reality and how they can be used to promote student’s engagement inside and outside of the classroom.